Sensitive Assembly: Gamifying the design and assembly of façade wall prototypes. (March 2016) - Savov, Anton; Tessmann, Oliver; Nielsen, Stig Anton
The article describes a method for gamifying the design and assembly of computationally integrated structures built out of discrete identical blocks. As a case study, the interactive installation Sensitive Assembly was designed and built at the Digital Design Unit (Prof. Dr Oliver Tessmann) at the Technische Universität of Darmstadt and exhibited during the digital art festival NODE 2015 in Frankfurt in 2015. Sensitive Assembly invites people to play a Jenga-like game: starting from a solid wall, players are asked to remove and replace the installation's building blocks to create windows to a nurturing light while challenging its stability. A computational system that senses the current state of the wall guides the physical interaction and predicts an approaching collapse or a new light beam breaking through. The installation extends the notion of real-time feedback from the digital into the physical and uses machine-learning techniques to predict future structural behaviour.